Encadrement Parental Et Developpement Emotionnel Des Adolescents Dans La Ville De Maroua, Cameroun - Mohamadou, Galy (European Scientific Journal, ESJ, 2018)
This study examines the correlation between parental supervision and emotional development among adolescents in the city of Maroua. A sample of two hundred and fifty (250) adolescents aged 11 to 19 has been selected through a simple random sampling selection. These data were subjected to the linear simple regression test. The results show that there is a correlation between parental supervision and the emotional development of adolescents. After analyzing the data collected, the hypotheses formulated on the different parental styles are: the authoritarian style (4.3%), the democratic style (3.6%), the permissive style (48%) and the careless style (4.7%), which states that parental supervision impacts on emotional development, have been confirmed. In the light of this study, it is established that what the adolescent experiences in his emotional development in the family context affects him decisively to be transposed to school and produce negative or positive effects depending on the case.